Paradox Peers: A Relational Approach to Navigating a Business–Society Paradox - Deeds Pamphile, Vontrese (Academy of Management Journal, 2022)
Despite advancements in our understanding of organizational paradox, we know little about how individuals navigate paradox when tensions are core to one’s occupational role, but not a dominant conc...